Unlocking the therapeutic potential of RNA: a comprehensive review of RNA-based therapy - Ahmad, Rafid Uddin; Pathak, Soumya (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2023.